TRANSCRIPT OF PROCEEDINGS HEARING ON NON SMOKERS RIGHTS ACT OF 1985 (Tufts Archival Research Center, 2007)
Transcript of proceedings at the hearing on the Non-Smokers Rights Act of 1985. Includes statements from the American Medical Association, the Tobacco Institute, the National Vietnam Veterans Coalition, the Agency for International Development, and Georgians Against Smoking Pollution.